1864 Id. Sess. Laws 442, An Act Concerning Crimes and Punishments, § 39 - (:unkn) unknown (General Publisher, 1864)
Prohibited dueling. Violators imprisoned not less than two nor more than five years in territorial prison. If any person shall have agreed to duel and caused death to any person from an injury resulting from the duel, they shall be found guilty of murder within one year and one day and punished accordingly.
--
Keywords: DUELING